2020
DOI: 10.1007/s42770-020-00353-7
|View full text |Cite
|
Sign up to set email alerts
|

Cellular response of Brevibacterium casei #NIOSBA88 to arsenic and chromium—a proteomic approach

Abstract: Cellular response against different heavy metal stress differs with the metal. Arsenic and chromium are heavy metals and toxic to living systems. The concentration of these metals in seawater is very low. However, due to their solubility in nature, they actively enter cells via various transport mechanisms and cause damage to the cells. Brevibacterium casei #NIOSBA88, a marine-derived, gram-positive isolate was multi-metal tolerant. Proteomic analysis of this isolate in response to arsenic and chromium resulte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 55 publications
(79 reference statements)
2
5
0
Order By: Relevance
“…The majority of the genes encoding protein translational machinery (ribosomal proteins) and proteins involved in amino acid metabolism were downregulated in response to arsenite. This finding is consistent with previous studies showing a decline in the rate of protein synthesis in response to arsenite As(III) exposure [ 52–54 ]. In addition, genes involved in oxidative phosphorylation pathways such as ATP synthase subunits A, C, δ and β, cytochrome ubiquinol oxidase subunits, and genes involved in intracellular protein transport, including secD , secF , secG and secE , were also downregulated in response to arsenite treatment.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The majority of the genes encoding protein translational machinery (ribosomal proteins) and proteins involved in amino acid metabolism were downregulated in response to arsenite. This finding is consistent with previous studies showing a decline in the rate of protein synthesis in response to arsenite As(III) exposure [ 52–54 ]. In addition, genes involved in oxidative phosphorylation pathways such as ATP synthase subunits A, C, δ and β, cytochrome ubiquinol oxidase subunits, and genes involved in intracellular protein transport, including secD , secF , secG and secE , were also downregulated in response to arsenite treatment.…”
Section: Discussionsupporting
confidence: 94%
“…The transcriptome data also showed upregulation of four DEGs, CheW, CheA, MotD and methyl-accepting chemotaxis protein, suggesting a role in the chemotaxis response towards arsenite. Upregulation of genes involved in carbohydrate metabolism pathways was also in agreement with previous studies [51, 52].…”
Section: Discussionsupporting
confidence: 92%
“…These compounds are usually found in mine tailings [5]. All five genera have previously been reported to be resistant to several heavy metals, such as chromium, nickel, zinc, copper, lead, cadmium, cobalt and mercury [36,37,[46][47][48][49][50][51][52]. This characteristic renders them potentially suitable for the biotreatment of gold mine tailings.…”
Section: Discussionmentioning
confidence: 99%
“…and Exiguobacterium spp. shows that under metal stress [in the presence of 750 mg L −1 arsenic; As(III) and As(V)] conditions, various housekeeping proteins (ribosomal proteins or lipid metabolism-related proteins) are downregulated while proteins like superoxide dismutase, thioredoxin disulfide reductase, lipid hydroperoxide reductase, ArsR, ArsA, Cdr (encoding Co-enzyme A disulfide reductase), and ABC transporter are be upregulated (Castro-Severyn et al, 2019;Shah and Damare, 2020). Additionally, transcriptome analysis by Liu et al (2020) also revealed the upregulation of areB gene in plant growth-promoting Paenibacillus polymyxa YCO136 in the presence of root exudates of tobacco.…”
Section: Resistance For Arsenic (As)mentioning
confidence: 99%